Pequenas mudanças grandes trajetórias? do Estatuto do Estrangeiro (1980) à Lei de Migração (2017) - Gonella, Yasmin Sousa (2023)
International migration has been a constant global appearance, and Brazil is no exception, experiencing different cycles and moments throughout its history. Migratory movements to Brazil were influenced by government regulations that sometimes encouraged and sometimes discouraged such processes. In this context, the general objective of this study is to analyze, through a process tracing approach, the transformations in Brazilian migration policy in the period from 1980 to 2017. Starting from the hypothesis that Brazilian migration policy predominantly follows an incremental pattern, interspersed with moments of rupture and transition to a new balance, this study employs concepts related to migration issues, in addition to the conceptual and methodological transport of public policy theories. To understand the present, the main normative aspects of Brazilian migration policy in the last two years will be explored, using governments as a chronological reference, not only to understand what legislatively was done, but also the importance given to the migration issue in the agenda of Brazilian politics. The theoretical basis will be provided by incremental and punctuated equilibrium theories, which will serve as tools to elucidate periods of stability and change in regulations, thus testing the initial hypotheses. The results reveal complex patterns of continuity and transformation, revealing that incrementalism and punctuated equilibrium are useful to explain different aspects of Brazilian migration policy. This research contributes not only to a deeper understanding of the evolution of Brazilian migration policy, but also to the broader literature on public policy theories, providing insights into the interconnection between the concepts of incrementalism, punctuated equilibrium in the analysis of migration policies. The results have important implications for policymakers, researchers and stakeholders in migration governance.